Quantification of volcanic cloud top heights and thicknesses using A‐train observations for the 2008 Chaitén eruption. Issue 7 (13th April 2015) - Prata, A. T.; Siems, S. T.; Manton, M. J.
Abstract New evidence of vertically thin (< 400 m), low‐level (< 10 km) volcanic ash clouds, as well as confirmation of previously reported high‐level (>10 km) ash clouds, from the May 2008 Chaitén eruption in southern Chile is presented. A‐train remote sensors were used to measure high‐resolution volcanic cloud top heights (VCTHs) during the explosive phase (2–10 May 2008) of the eruption. Ash clouds were identified using a reverse absorption technique applied to hyperspectral measurements taken by the Atmospheric Infrared Sounder. Once identified, heights and thicknesses were derived from the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument. As these two instruments are part of the same constellation of satellites, coincident retrievals are routinely possible. Collocation of the data allowed for detection of volcanic ash within CALIOP profiles. Using a simple thresholding algorithm, VCTH and thickness were derived from the CALIOP profiles. A total of 12 VCTH measurements, ranging from 3.7 to 16.6 km, have been derived. Back trajectories from the Hybrid Single Particle Lagrangian Integrated Trajectory dispersion model were used as a check on volcanic origin of the detected ash clouds. Ensemble forward trajectories were generated to demonstrate how the new data could be used to improve Volcanic Ash Advisory Center operations. The findings reported here demonstrate several cases where low‐level ash was not recorded previously and include observations of thin ash clouds at large distances (∼4000 km) from the volcano.